255 INCREASED TRANSIENT OUTWARD CURRENT, SHORTENED ACTION POTENTIAL DURATION AND "SHORT-QT SYNDROME" IN NA+/CA2+ EXCHANGER KNOCKOUT MICE. (1st January 2006) - Pott, C.; Ren, X.; Jordan, M. C.; Roos, K. P.; Philipson, K. D.; Goldhaber, J. I.
Abstract : Shortening of the ventricular action potential (AP) is a critical mechanism for the maintenance of Ca 2+ homeostasis and contractility in cardiac-specific Na + -Ca 2+ exchanger (NCX) knockout (KO) mice. The shortened AP limits Ca 2+ influx and increases efficiency of SR Ca 2+ release. To investigate the hypothesis that up-regulation of the transient outward current (Ito ) shortens the AP in KO myocytes, we recorded Ito in patch-clamped myocytes isolated from NCX KO mice. The pipette solution contained (in mM) 130 KCl, 5.4 NaCl, 1 MgCl2, 10 HEPES, 5 MgATP, 0.1 cAMP, pH 7.2 with KOH. Na + and Ca 2+ currents were blocked by nifedipine (2 μM) and TTX (10 μM) in the external solution, which also contained (in mM) 136 NaCl, 5.4 KCl, 10 HEPES, 1 MgCl2, 0.33 NaH2 PO4, 1 CaCl2, 10 glucose, pH 7.4 with NaOH, 26°C. Ito was increased in KO versus WT when cells were depolarized from -80 mV to potentials ranging from -60 to +50 mV (KO: 41 ± 3 pA/pF at +50 mV; n = 13; WT: 20 ± 2 pA/pF at +50 mV; n = 16; p (.01). Ito decay kinetics were also slower in KO. Consistent with increased Ito, electrocardiograms from KO mice exhibited shortened QT intervals (WT: 51 ± 4 ms; n = 8; KO: 38 ± 2 ms; n = 8; p < .05). Expression of the Ito-generating K+ channel subunit Kv4.2 was up-regulated in KO (n = 4; 78 ± 22%; p < .01), whereas no alteration of Kv4.3 and only a slight increase in KChip were detected. We conclude that shortening of the AP in KO myocytes is caused by an increase in Ito due to up-regulation of Kv4.2 protein expression. Since Kv4.2 expression is regulated by Ca 2+, we hypothesize that altered Ca 2+ handling in NCX KO mice leads to up-regulation of Kv4.2. which. in turn. reduces AP duration and limits Ca 2+ influx. This may comprise an important negative feedback mechanism against Ca 2+ overload in situations of reduced myocyte Ca 2+ extrusion capacity such as during myocardial ischemia.